Olonkho Comparisons: Stability and Transformations (based on the Texts from the Northern Epic Tradition of the Yakuts) - S. D. Lvova (Научный диалог, 2020)
The results of a comparative analysis of options for staible comparisons characteristic of the northern epic tradition of the Yakuts are presented. The relevance of the study is due to insufficient research of comparisons on the material of epic texts of the northern regions matching the established traditions of the olonkho of the central and Vilyuy regions of Yakutia to identify their commonality and specificity. Particular attention is paid to the structure of comparative constructions, their parallelization and the content of comparison images. A detailed analysis of the components of the five stable comparisons operating in all four texts is provided. As a result of the study, increased stability of comparisons was established in the Verkhoyansk, Mom and Oymyakon texts of the olonkho, in which only the peripheral part varies (epithets, additional terms of parallelism). The author’s notable introduction of the narrator in the Middle Kolyma text is considered, where peculiar objects and images of comparison are revealed. A comparison image was found that is characteristic only of the northern epic tradition when describing the heroic table. The definitions of individual obsolete words and their interpretation with the aim of establishing the original images of olonkho are given. A definition of the word kunnyalyk , missing in the dictionaries of the Yakut language, used as an epithet, included in the comparison construction and as a designation of an independent reference standard is proposed.